2013
DOI: 10.1002/ece3.651
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration of a parasite‐induced immune response in wild birds: Darwin's finches and introduced nest flies

Abstract: Ecological immunology aims to explain variation among hosts in the strength and efficacy of immunological defenses. However, a shortcoming has been the failure to link host immune responses to actual parasites under natural conditions. Here, we present one of the first experimental demonstrations of a parasiteinduced immune response in a wild bird population. The recently introduced ectoparasitic nest fly Philornis downsi severely impacts the fitness of Darwin's finches and other land birds in the Gal apagos I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
139
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 64 publications
(143 citation statements)
references
References 50 publications
3
139
1
Order By: Relevance
“…P. downsi had a significant negative effect on the reproductive success of birds in this study; see Koop et al (2013) for details. However, neither the body condition nor hematocrit of adult females differed significantly between parasite treatments.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…P. downsi had a significant negative effect on the reproductive success of birds in this study; see Koop et al (2013) for details. However, neither the body condition nor hematocrit of adult females differed significantly between parasite treatments.…”
Section: Discussionmentioning
confidence: 64%
“…The simplest explanation is that P. downsi is not a significant stressor for adult female birds. While previous studies suggest that female finches are bitten by P. downsi (Huber et al, 2010; Koop et al, 2013), the frequency with which this occurs is unknown. Our study did not find a significant difference in hematocrit values between females sitting on parasitized and non-parasitized nests.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Adult flies, which are not parasitic, lay their eggs in the nests of finches and other land birds in the Galápagos. In some years, 100% of finch nests fail to produce fledglings due to P. downsi (Koop et al 2011, 2013a, O'Connor et al 2013. Several studies have shown that P. downsi reduces the reproductive success of the medium ground finch (Geospiza fortis) and other species of Darwin's finches (reviewed in Koop et al 2011).…”
mentioning
confidence: 99%